Optimizing the quality of service excellence through the application of technology in tourism destination - Elvis Aguilera; Gefira Mokoginta; M Kresna Daffa Marta Lingga; Hesti Purwaningrum (Journal of Rural Tourism, 2025)
Purpose - The purpose of this study is to determine how the application of technology can impact the quality of excellent service at Bale Tirto, a tourism destination with a Javanese heritage concept located in Kiringan, Ponggok, Polanharjo, Klaten. Methodology/Design/Approach - The study uses a qualitative approach, gathering data through observation and interviews. It focuses on understanding the current manual operational system at Bale Tirto, such as handwritten bookkeeping and ordering, and how the introduction of technology can improve performance and service quality.Finding - The findings show that the application of technology at Bale Tirto has led to improved employee knowledge and ability to operate technology. This, in turn, has made the services provided to tourists and customers more optimal and efficient, resulting in enhanced service quality and overall performance.Originality/Value - This research highlights the significant role that technology can play in improving service quality at tourism destinations. By shifting from manual to technological systems, the study demonstrates how operational efficiency can be enhanced, leading to better customer experiences and improved business performance at Bale Tirto.